A new forest pest in Europe: a review of Emerald ash borer (Agrilus planipennis) invasion. (25th October 2016) - Valenta, V.; Moser, D.; Kapeller, S.; Essl, F.
Abstract: In this publication, we review the biology, ecology, invasion history, impacts and management options of Emerald ash borer (EAB) Agrilus plannipennis, with a particular focus on its invasion in Europe. Agrilus planipennis (EAB) is a wood‐boring beetle native to East Asia. Having caused massive damages on ash species in North America in the last decades, it was first recorded in Europe in 2003 in Russia (Moscow). All ash ( Fraxinus ) species native to Europe and North America are known to be susceptible to EAB attacks, which cause high tree mortality even among formerly healthy trees. Recorded expansion rates are between 2.5 and 80 km/year in North America and between 13 and 41 km/year in European Russia. Given current expansion rates, EAB is expected to reach Central Europe within 15–20 years. A combination of mechanical, biological and chemical control and phytosanitary measures may reduce its impact, which nevertheless most likely will be substantial. There is an urgent need to identify native enemies in Europe, to test suitable biocontrol agents and to develop early detection and management measures. Although it is obvious that EAB will become a major pest in Europe, early and dedicated response will likely be able to reduce the level of ash mortality, and thus improve the opportunity for long‐term survival of ash as an important component in European forests.